2012
DOI: 10.1177/1756287212461681
|View full text |Cite
|
Sign up to set email alerts
|

The role of naftopidil in the management of benign prostatic hyperplasia

Abstract: Naftopidil, which to a certain extent shows an affinity to α 1D -adrenoceptor subtype in addition to a high affinity to α 1A -adrenoceptor, has been used for the treatment of benign prostatic obstruction and benign prostatic hyperplasia (BPH) associated lower urinary tract symptoms (LUTS). The aim of the present review is to systematically refer to the published studies on this unique agent for BPH. Based on a randomized prazosin-controlled study and another double-blind placebo-controlled study, which verifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 36 publications
(48 reference statements)
0
13
0
Order By: Relevance
“…As naftopidil can inhibit the release of adenosine triphosphate (ATP) from the bladder epithelium (8,27), it may facilitate the afferent nerves and evoke the micturition reflex. Clinical studies that have examined the various agents that can improve urine storage symptoms have demonstrated that naftopidil exhibits a clear superiority over the other α1A blockers (6). This action may be related to multiple effects on the cerebrum, spinal cord, and bladder epithelium.…”
mentioning
confidence: 99%
“…As naftopidil can inhibit the release of adenosine triphosphate (ATP) from the bladder epithelium (8,27), it may facilitate the afferent nerves and evoke the micturition reflex. Clinical studies that have examined the various agents that can improve urine storage symptoms have demonstrated that naftopidil exhibits a clear superiority over the other α1A blockers (6). This action may be related to multiple effects on the cerebrum, spinal cord, and bladder epithelium.…”
mentioning
confidence: 99%
“…For example, nonselective AR antagonist alfuzosin causes hypotension without ejaculation problems; on the other hand, tamsulosin causes ejaculation problems without hypotension [24,25]. Meanwhile naftopidil shows minimal effects on the cardiovascular system and ejaculatory function [26]. Further studies of add-on therapy to maximize the treatment efficacy or minimize the side effects might provide an opportunity to find a new modality.…”
Section: Discussionmentioning
confidence: 99%
“…Naftopidil, an α1D/A blocker, attenuates urethral outflow resistance in smooth muscle relaxation of the bladder neck and prostatic urethra, and is used to treat benign prostatic hyperplasia . Clinically, the effect of naftopidil is excellent compared to other α1 blockers for urine storage disorders such as nocturia . In animal experiments, microinjection of naftopidil into the medial frontal lobe or intrathecal injection of naftopidil suppresses the micturition reflex .…”
Section: Introductionmentioning
confidence: 99%